2016
DOI: 10.5567/pharmacologia.2016.103.113
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activities and Chemical Constituents of Extracts from Cordyline fruticosa (L.) A. Chev. (Agavaceae) and Eriobotrya japonica (Thunb) Lindl, (Rosaceae)

Abstract: Background and Objective: Cordyline fruticosa (Agavaceae) and Eriobotrya japonica (Rosaceae) are two medicinal plants used for the treatment of various diseases such as infections of mammary glands, sore throat and neck pain for the first plant, diabetes, cough, ulcers, protection against oxidative stress and cognitive deficits for the latter. The present study was designed to evaluate the antioxidant activity of the different extracts of these two plants as well as to isolate and identify their chemical const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 21 publications
1
3
0
1
Order By: Relevance
“…(2) Results show that activity of AgNPs is higher than the water extracts, which is also in line with the findings of higher amounts of TFC, TPC and TAC in AgNPs from this study. Similar studies have shown significant DPPH scavenging activity for methanolic extracts of Cordyline fruticosa leaves (Tapondjou et al, 2016).…”
Section: Quantitative Analysis Of Total Antioxidant Capacitysupporting
confidence: 72%
See 1 more Smart Citation
“…(2) Results show that activity of AgNPs is higher than the water extracts, which is also in line with the findings of higher amounts of TFC, TPC and TAC in AgNPs from this study. Similar studies have shown significant DPPH scavenging activity for methanolic extracts of Cordyline fruticosa leaves (Tapondjou et al, 2016).…”
Section: Quantitative Analysis Of Total Antioxidant Capacitysupporting
confidence: 72%
“…100% Water extracts and AgNP solutions were prepared and 2mL of 0.16mM DPPH solution was added. Mixtures were incubated in the dark for 15 minutes (Tapondjou et al, 2016). Absorbance was measured at 517nm using methanol as the blank.…”
Section: Dpph (22-diphenyl-1-picryl-hydrazyl-hydrate) Radical Scaveng...mentioning
confidence: 99%
“…However, their effects were significantly lower than the positive controls in both cases (p < 0.05). In addition, 5 was found to have antihypertensive, [46] antihemolytic, [47] antioxidant, [47,48] glucose tolerance-improving activity, [49] and inhibitory effect on amyloid-β aggregation. [48] The new compound 2 mildly inhibited platelet aggregation for both agonists.…”
Section: Structure Elucidation Of Two New Compoundsmentioning
confidence: 99%
“…Samples for NMR (nuclear magnetic resonance) experiments were performed in deuterated solvent, CD 3 OD, and analyzed using a Varian mercury-plus spectrometer, 400 MHz for 1 H. 1 H chemical shifts were reported in parts per million (ppm), while the coupling constant (J) was Hertz (Hz) (Figures S1-S3, Supplementary Materials) [48].…”
Section: Nmr Analysismentioning
confidence: 99%